PENGELOLAAN LIMBAH PLASTIK MENJADI BIOGAS DI PESISIR PANTAI GALESONG - Sri Winda; Sulkifli Sulkifli; Mustika Nur Hasanah; Nadya Nadya; Muhammad afindito Dzulkarnain; Sitti Khadijah Nurtika (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2022)
Population and economic growth causes an increase in waste production, especially plastic waste. Pyrolysis is the process of fracturing or breaking down polymer chains into simpler compounds through a thermal process (heating/burning) with little or no oxygen. Plastic waste can be decomposed and converted into fuel which has a high calorific value through the pyrolysis process. This research aims to determine and compare the capabilities of plastic pyrolysis oil with kerosene and diesel in terms of density, burning time, water temperature and volume of water lost (evaporated) when cooked using the oil. The research results show that 1) the density of pyrolysis oil is 0.8 g/ml. The time required to completely burn an object is 4.02 minutes. Cooking water using pyrolysis fuel oil produces a temperature of 75°C at a cooking time of 4 minutes with a volume of water lost (evaporated) of 12.6 ml. 2) Of the 4 parameters observed, the quality of pyrolysis oil is below kerosene but above diesel oil.